MR Imaging of the Adnexal Masses: A Review - Ahmad, I; Kirimani, S; Rashid, M; Ahmad, K (Nepalese Journal of Radiology, 2012)
MR (magnetic resonance) imaging is a non invasive technique for evaluation of female pelvic masses. Due to its high spatial resolution and excellent tissue contrast, various masses of adnexal origin can be imaged and a confident diagnosis can be made. MRI helps to delineate normal anatomical structures and elucidate the pathological lesions. It has high sensitivity and specificity for differentiating benign adnexal masses from malignant ones. This review article gives a brief account of approach to adnexal masses based on tissue characterization on MR imaging. DOI: http://dx.doi.org/10.3126/njr.v1i1.6326 Nepalese Journal of Radiology Vol.1(1): 54-60